Traditional crop protection - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Natural crop protection based on local farm resources in the tropics and subtropics / Stoll, G. 1986. Josef Margraf, Aichtal, 186 pp. ISBN 3-924333-43-2